Port-Wine Stain Laser Treatments and Novel Approaches - Ortiz, Arisa E.; Nelson, J. Stuart (Facial Plastic Surgery, 2012)
Background and Objectives Port-wine stains (PWSs) are capillary vascular malformations that are commonly resistant to treatment. Currently, the pulsed dye laser (PDL) is the treatment of choice. Multiple treatments are required and complete blanching after laser irradiation is rarely achieved. We review current therapeutic modalities for PWSs and recent developments for enhanced clearance.Study Design/Materials and Methods Relevant literature was reviewed including PDL modifications for improved efficacy, alternative laser devices for treatment-resistant PWSs, and the addition of agents to modulate the wound-healing response after laser irradiation.Results Although PDL is the treatment of choice for PWSs, increased understanding of interactions between PWSs and PDL has led to improvements in therapeutic outcome in terms of lesion blanching.Conclusions Preliminary evidence of combination therapy using antiangiogenic agents after laser irradiation appears promising and could lead to the development of a new standard of care for PWSs.
Keywords: port-wine stains; capillary malformation; laser; selective photothermolysis; pulsed dye laser